2020
DOI: 10.21203/rs.3.rs-51964/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A large-scale database of T-cell receptor beta (TCRβ) sequences and binding associations from natural and synthetic exposure to SARS-CoV-2.

Abstract: We describe the establishment and current content of the ImmuneCODE™ database, which includes hundreds of millions of T-cell Receptor (TCR) sequences from over 1,400 subjects exposed to or infected with the SARS-CoV-2 virus, as well as over 135,000 high-confidence SARS-CoV-2-specific TCRs. This database is made freely available, and the data contained in it can be downloaded and analyzed online or offline to assist with the global efforts to understand the immune response to the SARS-CoV-2 virus and develop ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
255
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(261 citation statements)
references
References 9 publications
3
255
2
1
Order By: Relevance
“…We investigated the degree to which the MIRA enrichment strategy employed by Nolan et al (2020) identified TCRs with identical or similar amino acid sequences. In general, across multiple MIRA TCR β-chain antigen-enriched repertoires, the proportion of amino acid TCR sequences observed more than once was generally lower than in the tetramer-enriched repertoires and varied considerably across the sets; some MIRA sets resembled tetramer-sorted sub-repertoires (Figure 1B; see MIRA133), while others were more similar to unenriched repertoires (Figure 1B; see MIRA90).…”
Section: Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…We investigated the degree to which the MIRA enrichment strategy employed by Nolan et al (2020) identified TCRs with identical or similar amino acid sequences. In general, across multiple MIRA TCR β-chain antigen-enriched repertoires, the proportion of amino acid TCR sequences observed more than once was generally lower than in the tetramer-enriched repertoires and varied considerably across the sets; some MIRA sets resembled tetramer-sorted sub-repertoires (Figure 1B; see MIRA133), while others were more similar to unenriched repertoires (Figure 1B; see MIRA90).…”
Section: Frameworkmentioning
confidence: 99%
“…(A) Framework: sets of CD8+ TCRs activated by SARS-CoV-2 peptides were previously discovered in 61 individuals diagnosed with COVID-19 using a Multiplex Identification of Antigen-Specific T Cell Receptors Assay (MIRA) by Nolan et al (2020). For each TCR clone activated by a given peptide, we used tcrdist3 to evaluate the repertoire fraction spanned at different TCRdist radii within (i) its antigen enriched repertoire (black) and (ii) a control V- and J-gene matched, inverse probability weighted background repertoire (purple).…”
Section: Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…B-cell linear and discontinuous epitope prediction tools have been used by researchers to identify possible SARS-CoV-2 epitopes (23)(24)(25). Several more recent studies experimentally determined SARS-CoV-2 immune epitopes (11,26,27). Interestingly, several groups have reported signi cant T-cell reactivity against SARS-CoV-2 epitopes in individuals without virus exposure (22,26,28,29).…”
Section: Introductionmentioning
confidence: 99%
“…B-cell linear and discontinuous epitope prediction tools have been used by researchers to identify possible SARS-CoV-2 epitopes (23)(24)(25). Several more recent studies experimentally determined SARS-CoV-2 immune epitopes (11,26,27). Interestingly, several groups have reported significant T-cell reactivity against SARS-CoV-2 epitopes in individuals without virus exposure (22,26,28,29).…”
Section: Introductionmentioning
confidence: 99%